The effect of breast support and breast pain on upper-extremity kinematics during running: implications for females with large breasts - White, J.; Mills, C.; Ball, N.; Scurr, J. (Journal of Sports Sciences, 2015)
The relationship between inappropriate breast support and upper-extremity kinematics for female runners is unclear. The purpose of this study was to investigate the effect of breast support and breast pain on upper-extremity kinematics during running. Eleven female recreational runners with larger breasts (UK D and E cup) completed a 7 min 20 s treadmill run (2.58 m/s) in a high and low breast support condition. Multi-planar breast and upper-extremity kinematic data were captured in each breast support condition by eight infrared cameras for 30 s towards the end of the run. Breast pain was rated at the end of each treadmill run using a numeric analogue scale. The high support bra reduced breast kinematics and decreased breast pain (P < 0.05). Upper-extremity kinematics did not differ between breast support conditions (P > 0.05), although some moderate positive correlations were found between thorax range of motion and breast kinematics (r = 0.54 to 0.73). Thorax and arm kinematics do not appear to be influenced by breast support level in female runners with large breasts. A high support bra that offers good multi-planar breast support is recommended for female runners with larger breasts to reduce breast pain